Bibliometric analysis of leader-member exchange theory related literature based on the Scopus database / Hao Wu, Anusuiya Subramaniam and Syafiqah Rahamat - Wu, Hao; Subramaniam, Anusuiya; Rahamat, Syafiqah (Research Management Institute (RMI), 2023)
The relationship between leaders and followers is the most common in an organisation. The degree of interaction between leaders and employees, widely known as leader-member exchange (LMX), significantly impacts employees’ attitudes and behaviours. Thus, through a systematic review of the literature on LMX, this study summarised the research hotspots, inconsistencies in current research, and trends for future studies. In addition to providing a reference for the development of theories, this study also helps enterprise managers better understand the positive role of LMX quality in the organisation. This study used bibliometrics to review 1,883 articles from the field of LMX based on the Scopus database. Excel and VOSviewer were used for linear regression, statistical analysis, and cluster analysis of the documents that met the requirements. Firstly, the temporal trends and sources of LMX were summarised, and it was found that publications grow exponentially. Secondly, out of 3,617 authors, 127 are core authors. Thirdly, the United States, China, Australia, the United Kingdom, and South Korea are the countries with the most study on the LMX theory. Fourthly, LMX has a wide range of applications. Finally, the clustering analysis of keywords shows five clusters.